Exploring the influence of façade design elements on tourist satisfaction: evidence from China - XiangYang Zhou; Li Li (Journal of Asian Architecture and Building Engineering, 2025)
With the COVID − 19 pandemic largely subsided, tourism has emerged again as a key driver of global economic recovery. Building façade design, a key component of destination image, significantly affects tourists’ satisfaction. However, systematic research remains limited. Focusing on two Chinese cities, this study employs the IPA – KANO model to prioritize 14 façade design elements and quantify their correlations with tourist satisfaction. The findings show that balconies, façade decorations, night lighting, and vertical greening significantly influence satisfaction levels. Specifically, façade decorations and night lighting exhibit strong positive correlations with overall satisfaction. Furthermore, the study offers urban planners, architects, and tourism managers evidence – based strategies for enhancing destination appeal through optimized façade design.